Diseases of Plantation Trees in Fiji Islands I Brown Root Rot of Mahogany (Swietenia macrophylla King) - Singh, Sujan; Bola, Irami; Kumar, J. (Indian Forester, 1980)
Extensive mortality in mahogany plantations in Fiji Islands was found due to decay of roots by Fomes noxius. Main disease symptoms include brown incrustation on the bark and white pocket rot in the wood of roots and stems of affected trees. The disease spreads strictly by root contact. Primary infection takes place through contact of mahogany roots with infacted roots of felled or poisoned standing trees of the original forest. Subsequent spread in lines takes place through root contact between diseased and healthy mahogany plants. Plants upto 10 years age may be killed out right while in older plants, the disease establishes as butt rot. Pruning of tap root before planting was found to have encouraged the development of more lateral roots than in plants raised from direct seed sowing. An attempt was made to identify the species of infection sources in 1967, 1969, 1970 and 1971 plantations. In 44 infection centres, 15 species of natural forests were identified which had been colonized by F. noxius and thus had served as source of infection to mahogany plants. F.noxius was found to attack and kill many tree species in natural forests but infection centres were confined to limited areas only. Measures are outlined for future work on possible control of the disease.